1963
DOI: 10.1042/bj0860226
|View full text |Cite
|
Sign up to set email alerts
|

Acidic peptides of the lens. 8. S-(α β-dicarboxyethyl) glutathione

Abstract: The presence of a number of unidentified acidic peptides in extracts of calf lens was recorded by Waley (1956). Electrophoresis separated these compounds into a 'slow acid' fraction and a 'fast acid' fraction. The main new constituents of the former are ophthalmic acid (y-glutamyl-m-nbutyrylglycine) and norophthalmic acid (y-glutamylalanylglycine; Waley, 1957, 1958). The fast acid fraction was further subdivided into fractions called 1ca and 1 P. The main constituent of 1 a is S-sulphoglutathione (Waley, 1959)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1963
1963
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…The two substances were measured in separate runs by the present HPLC method, to avoid the problem of overlapping peaks in the stimultaneous determination. Calam & Waley reported that the conoentration of S-(l,2-dicarboxyethyl)glutathione was 30 >1/100 g of calf lens and that of S-(l,2-dicarboxyethyl)L-cysteine was lower (1). This value of S-(l,2-dicarboxyethyl)glutathione in calf lens was about 3 times äs much äs that determined by us.…”
Section: Discussionsupporting
confidence: 49%
“…The two substances were measured in separate runs by the present HPLC method, to avoid the problem of overlapping peaks in the stimultaneous determination. Calam & Waley reported that the conoentration of S-(l,2-dicarboxyethyl)glutathione was 30 >1/100 g of calf lens and that of S-(l,2-dicarboxyethyl)L-cysteine was lower (1). This value of S-(l,2-dicarboxyethyl)glutathione in calf lens was about 3 times äs much äs that determined by us.…”
Section: Discussionsupporting
confidence: 49%
“…S-(1,2-dicarboxyethyl)glutathione is typically found in the lens in considerable amounts (Calam and Waley, 1963). In the present study, it was detected in the cortex of normal and control lenses, and its abundance increased following HBO treatment, presumably due to an increase in either L-malate or fumarate, which are substrates for GSH-dependent formation of S-(1,2-dicarboxyethyl)glutathione (Tsuboi et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of maleic acid into rats has been reported to increase urinary excretion of this compound and the binding of maleic acid to tissue proteins [18]. Moreover, a free thiol group of cysteine is slowly alkylated in a solution containing maleic acid or fumaric acid to form S-(I ,2-dicarboxyethyl)-~-cysteine [14]. Modified mutant human lysozyme was produced in S. cerevisiue when mono[tris(hydroxymethyl)-aminomethane] maleate was added to the culture medium as one of buffer components, but not when it was excluded from the culture medium.…”
Section: Discussionmentioning
confidence: 99%